My Professor is Hot! Correlates of RateMyProfessors.com Ratings for Criminal Justice and Criminology Faculty Members - Crews, Angela D. (2012)
RateMyProfessors.com” ratings of the easiness, helpfulness, clarity, overall quality, and “hotness” of 407 criminal justice and criminology faculty members from across the United States were collected. Data were analyzed to determine what faculty characteristics determined these ratings. Experience working in the criminal justice field predicted higher ratings, while years of teaching experience was predictive of lower ratings. After controlling for instructors easiness and “hotness” ratings, the instructors’ ascribed characteristics (such as race and sex) explained the greatest proportion of variance in clarity, helpfulness, and overall quality scores. Professional characteristics, such as years of experience, publication rate, and possession of a doctorate were less influential on Ratemyprofessors.com scores